Pengaruh On Time Performance Terhadap Minat Beli Ulang Pada Maskapai Citilink Di Bandar Udara Internasional Husein Sastranegara Bandung - Difa Ardhiansyah Alfan (Universitas Sains dan Teknologi Komputer, 2023)
Air transport, including technology that can move a person from one place to another, is essentially air travel. Ownership of aircraft for passengers is usually owned by the airline. Airlines are companies that sell transportation services using air type transportation. In the world of aviation, On Time Performance is an element that can result in consumer loyalty to a service product. Passenger satisfaction is key to building profitable relationships with consumers, to retain and grow and accumulate passenger lifetime value. This research was conducted on August 1 – August 31, 2022, at Citilink airline at Husein Sastranegara International Airport Bandung. The type of research used in this study is descriptive research using a quantitative approach. The population used was Citilink Airlines passengers at Husein Sastranegara International Airport Bandung with a sample taken as many as 85 respondents. data were obtained through questionnaires and processed using Simple Linear Regression Analysis. The results of data processing show a positive influence between On Time Performance on Repurchase Interest in Citilink Airlines at Husein Sastranegara International Airport Bandung with a correlation coefficient of 0.821 with a guarantee coefficient (Koef. Determination) of 67.4%.